Heterozide Derivatives as Effective Additives to Cryoprotective Media - Kabachny, V. I.; Gorbunova, N. I. (Problems of Cryobiology and Cryomedicine, 2004)
We have investigated the effect of heteroside derivatives on succinate dehydrogenase (SDG), malate dehydrogenase (MDG), lactate dehydrogenase (LDG) activity and dynamics of fructose synthesis and uptake in bovine spermatozoa under normo-, hypothermia and cryopreservation conditions. The data obtained testify to the fact, that heteroside cryoprotective effect is stipulated by the activation of energy-producing enzymes. In addition, heterosides recover the activity of enzymes, damaged during cooling.